Editorial: Dynamic Biomarkers of Response to Anti-Immune Checkpoint Inhibitors in Cancer - Said Dermime (79420) (2021)
Immune checkpoint blockade (ICB) has been approved as first- or second-line therapy options in a broadening range of metastatic cancer and is increasingly explored in the treatment of early stage tumors. However, clinical responses are limited to a small group of patients and potentially long-lasting responses were observed in 10% to 40% of cancer patients, depending on the malignancy subtype. Considerable efforts have been made to identify predictive factors of response to ICB with the aim to use this therapy in patients with a high probability of response and to avoid exposing non-responder subjects to their potential side effects. Whilst a range of biomarkers have been investigated, their predictive potential remains unsatisfactory. In current clinical practice only PD-L1 expression in tumor tissues is used as predictive biomarker of response to PD-1 immune checkpoint blockade. However, a small proportion of patients with absent PD-L1 tumor expression may still respond to PD-1 blockade, making it difficult to restrict prescription of these therapies solely based on this biomarker. Hence, the search for novel biomarkers of response to checkpoint inhibitors remains an unmet need. One promising emerging approach is to focus on dynamic biomarkers, which would allow, when tested in the patient early after exposition to the therapeutic agents, to identify those patients presenting an immune response failure. The study of the dynamics of the immune system and of the tumor under immune checkpoint blockade shed light on their mechanisms of activity. Indeed, some immune pathways induced by ICB therapy may affect anti-tumor activity, whilst others may correlate with immune related adverse events (irAE) rather than with response. Moreover, tumor-intrinsic mechanisms of immune escape may develop following ICB and will consequently affect treatment outcome. We have recently summarized the dynamics of the immune system and of the tumor under immune checkpoint blockade. We emphasized the importance of studying mechanisms influencing response to ICB and focused on the multitude of immune cells subsets (including effector and immunosuppressive T cells and B cells subsets) that were shown to be impacted by CTLA-4 and PD-1/PD-L1 blockade monotherapy. In this Research Topic, we compiled reviews and original research articles reflecting the current advances in the study of dynamic biomarkers as predictors of the response to checkpoint inhibitors therapies in cancer. Four complimentary areas are addressed in this topic. Other Information Published in: Frontiers in Immunology License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.3389/fimmu.2021.781872